2015
DOI: 10.4314/ajtcam.v12i3.16
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous determination of flavonoids and triterpenoids in <i>Cyclocarya paliurus</i> leaves using high-performance liquid chromatography

Abstract: Background: Cyclocarya paliurus is an endangered plant and endemic to China. The leaves of C. paliurus have been used in drug formulations and as ingredients in functional foods in China. The aim of this study was to develop an effective method to extract most of the compounds and to establish a simplified HPLC analytical method to determine the contents of major bioactive compounds simultaneously. Materials and methods:High-performance liquid chromatography (HPLC) coupled with a photodiode array detector (PDA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…However, HPLC has emerged as the most widely used method in practice for its easy availability and relatively low price [ 25 , 31 , 32 ]. With respect to detection wavelength, more detectable common peaks and larger response values could be obtained at 205 nm due to the lack of a chromophore group in the chemical structures of triterpenoids, which show mainly terminal absorptions such as 205 nm in their UV spectra [ 21 , 23 ]. Hence, characteristic chromatographic patterns were obtained by using 205 nm as the detection wavelength.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, HPLC has emerged as the most widely used method in practice for its easy availability and relatively low price [ 25 , 31 , 32 ]. With respect to detection wavelength, more detectable common peaks and larger response values could be obtained at 205 nm due to the lack of a chromophore group in the chemical structures of triterpenoids, which show mainly terminal absorptions such as 205 nm in their UV spectra [ 21 , 23 ]. Hence, characteristic chromatographic patterns were obtained by using 205 nm as the detection wavelength.…”
Section: Resultsmentioning
confidence: 99%
“…Since most botanical extracts have the therapeutic or preventable effects based on the synergic effects of their multiple components and multiple targets, it is insufficient to determine merely several markers of bioactive constituents in the complex botanical extracts [ 18 ]. Unfortunately, recent studies on the quality control of C. paliurus are only focused on a few selected flavonoids such as isoquercitrin, kaempferol and quercetin or a few selected triterpenoids because many marker components are not commercially available, especially some unique constituents originating from C. paliurus [ 19 , 20 , 21 ]. Obviously, the current analysis on bioactive constituents was insufficient to reflect the complexity and synergistic actions of multiple components in leaves of C. paliurus.…”
Section: Introductionmentioning
confidence: 99%
“…C. paliurus is generally known as the sweet tea tree, and its leaves are used to cure fever, detoxify, and alleviate pain [ 3 ]. Moreover, it was widely used in ancient China to make a medicinal tea [ 4 ]. Recently, various studies have found that many potentially bioactive compounds in the leaves of C. paliurus , including polysaccharides, proteins, minerals, phenolic compounds, vitamins, saponins, sugars, triterpenoids, and amino acid have beneficial effects on antihypertensive activity, hypoglycemic activity, hypolipidemic activity, and antioxidant activity [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Cyclocarya paliurus (Batal.) Iljinskaja, also known as the money tree, belongs to the family Juglandaceae and is one of the endangered medicinal plants protected by the state ( 1 – 4 ). Cyclocarya paliurus is a tall and fast-growing deciduous tree 10–30 m high that is widely distributed in the subtropical provinces of China ( 5 ).…”
Section: Introductionmentioning
confidence: 99%